Legislation about consumer rights protection in the foreign countries: rather-legal analysis - Sultanova, A.T.; Lavnichak, A. (Bulletin of the Karaganda University “Law Series”, 2019)
The article analyzes Consumer Protection Legislation of foreign countries, in particular, the United States, Great Britain, European Union member states and the Commonwealth of Independent States, the Eurasian Economic Union in accordance with the UN Guidelines for Consumer Protection (1985). The world experience in the field of consumer protection, legislative acts regulating consumer rights and the activities of public organizations in this area are also analyzed. The authors deals with the legal mechanisms for consumer rights’ protection and restoration in Kazakhstan in cases of defective goods sale, the consumers’ right to exchange or return non-conforming goods in comparison with the 2015 UK Consumer Rights Act. The authors concluded that legislation of advisory nature adopted within the CIS and the EEC framework is intended to define general legal and institutional basis for the consumer protection, and they are not imperative. The level of ensuring consumer rights of citizens in the CIS countries is not in line with international standards yet. In this regard, the authors propose to develop a new legal mechanism for the consumer rights protection.